THE IMPACT OF SYNERGY BETWEEN ICB AND ISLAMIC FINTECH LENDING ON THE ICB’S FINANCIAL PERFORMANCES - Muhammad Anif Afandi; Slamet Tedy Siswoyo (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2021)
The synergy between Islamic financial institutions is one key in the development of Islamic economics as stated in the Masterplan for Islamic Economics of Indonesia 2019 - 2024. In 2018, three Islamic Commercial Banks (ICB), namely Bank Mega Syariah (BMS), Bank BNI Syariah (BNIS) and Bank Syariah Mandiri (BSM) conducting synergy with Islamic FinTech lending in the form of shadow investors. Through this study carried out analysis of the impact of synergy between ICB and Islamic FinTech lending on the ICB’s financial performances as one reflection of the success of the synergy and economic indicators that reflect the responsibility of the ICB to the regulator. Wilcoxon signed-ranks test is used as a data analysis technique with the results of study showing that sequentially the synergy most profitable for the BSM because of the positive impact on financial performances, especially in the aspect of capital, profitability, efficiency and asset quality. While, for BNIS known synergy has a positive impact on financial performances, especially in the aspect of capital, liquidity and efficiency. Meanwhile, for BMS is known that the synergy only has a positive impact on financial performances, especially in the aspect of asset quality. The results of this study are beneficial for the ICB, Islamic FinTech lending as well as the regulator as material to the evaluation or formulation of policy regarding synergy between ICB and Islamic FinTech lending in Indonesia.